Expanding the infrarenal aortic aneurysm repair to nonagenarians: the role of evar - Teixeira,Sérgio (2017)
Introduction: Advanced age negatively impacts the outcomes of abdominal aortic aneurysm (AAA) repair. Nowadays, endovascular procedures enable vascular surgeons to treat elderly patients who cannot be submitted to open surgery. Aims: We report our experience with endovascular aneurysm repair (EVAR) in nonagenarians. Methods: We retrospectively reviewed our prospectively maintained aneurysm database in order to obtain records of all patients more than 90 years-old, who were submitted to EVAR over a 12 years period at our institution. Patients' comorbidities, functional status, aneurysm size, perioperative complications, endoleaks, reinterventions and long-term survival were recorded. Results: 171 EVAR procedures were performed. Three (1,75%) nonagenarians underwent aneurysm repair (3 male; mean age 91.3 ± 1.25 years). Mean aneurysm diameter was 8.2 ± 1.68 cm with a median size of 8.1 cm (range 6.2-10.3 cm). There were 1.7 mean comorbidities per patient. Technical success rate was 100%. Mean hospital length of stay was 4.3 ± 0.47 days with a median of 4 days (range 4-5 days). Thirty-day mortality was 0%. Mean follow-up and mean survival were 28 months. There were no complications and all patients returned to their preoperative functional status. No endoleaks were identified on the follow-up imaging. Conclusions: We have shown, in a small and carefully selected group, that EVAR is associated with good outcomes in nonagenarian patients. EVAR is, in our opinion, the best treatment option for AAA in nonagenarians with good functional status.